Individual Reflections: To Assess The Viability of A New Service Concept and To Develop A Comprehensive Business Plan for An Energy Management Consultancy (EMREG) - Ansong, Lilian Owusu Afriyie (2012)
The purpose of this study was to establish the feasibility and viability of a proposed new, high profile, specialist B2B service called Part Time Energy Management. Based on this, a business plan was to be developed in order to identify the most appropriate strategies for EMREG to pursue in delivering this service. The research included both primary and secondary research. A review on current literature with a focus on New Service Development (NSD) was carried out. The primary research included in-depth interviews with 11 participants from SMEs and energy professionals across different organisations. The research findings indicate that there is indeed a market for the PTEM concept proposed by EMREG. This need is however met by the major challenges specifically of time and financial constraints that SMEs face to implement energy management systems in general. The analysis indicates that EMREG needs to differentiate its service based on Boutique 2 strategic group and focus on niche markets. Further research indicates that EMREGs primary, secondary and tertiary target customers fall within the group of SMEs with employee number of between 50-199, 20-49 and 200-250 respectively. Additionally, the South East and North West regions are identified as primary regions for manufacturing, transportation and storage industries. The competitor analysis also reveals that there is no competitor solely focused in part time energy management concept. The financial analysis indicates that the PTEM service will save an average of 10% of total energy spending of the client from the primary segment. This works to a forecasted first and second year projections turnover of £78,705 and £808,913. Profit margins are calculated as -8.15% and 27.94% in consecutive years. It is estimated that EMREG will achieve a break even sales volume off £400,000 within 18 months’ of commencement. On marketing, it is identified that focus should be placed on promotions, sales tactics, pricing and people. The critical risks identified with this service are: competition from utilities companies, availability of human capital, technology, control and accountability, reputational risk. In conclusion, the PTEM concept is a viable on considering the inefficiencies within the SME sector. EMREG can achieve great success in this industry with a clear and unique value proposition in addressing this need. Despite this, there is some significant threat as far as imitability of this concept is concerned, together with other risks associated with finances. EMREG should therefore pursue this strategy but with caution.